Halal Food Traceability System using AI and Blockchain - Alourani, Abdullah; Khan, Shahnawaz (Journal of Posthumanism, 2025)
The demand for halal food products is increasing rapidly around the world. The consumption of halal food products is just not among Muslims but also non-Muslims, due to the purity of the halal food products. However, there are several challenges that are faced by halal food consumers. The challenges raise doubt among the halal food consumers about the authenticity of the product being halal. Therefore, a solution that can address these issues and establish trust between consumers and producers is needed. Blockchain technology can provide a distributed ledger with an immutable record of the information. Artificial intelligence supports developing a solution for pattern identification. The proposed research utilizes blockchain an artificial intelligence-based system for developing and e-adoption of a system that ensures the authenticity of halal food products by providing traceability related to all the operations and processes of the supply chain and sourcing the raw material. The proposed system has been tested with a local supermarket in a sandbox environment. The results and tests of the developed solution seemed effective and the testers expressed interest in real-world implementation of the proposed system. Therefore, the findings contribute to the knowledge of technology adoption by examining the application of the proposed system in halal food supply chain and provide insight into the potential benefits for e-adoption in this domain.